Modeling Studies of Gravity Wave Dynamics in Highly Structured Environments Reflection, Trapping, Instability, Momentum Transport, Secondary Gravity Waves, and Induced Flow Responses - Dong, Wenjun (Journal of geophysical research. Atmospheres : JGR, 2022)
© 2022. The Authors.